Proposta de gerenciamento de resíduos de serviço de saúde domiciliar no município de Apucarana - PR - Silva, Priscila Longo Silvestre da (2021)
The Sistema Único de Saúde (SUS) governs the current Brazilian Health System and is based on principles such as Universality, Integrality, Individuality, Equity, Solidarity and Humanization of Health Care. In recent years, home care has increased significantly. In this type of caring, the patient is allowed to remain at home with the use of some hospital resources that guarantee medical care, monitoring by a multidisciplinary team, in addition to the participation of the family in the care. The Waste from Health Services (WHS) is the waste that carries a load of toxic components that must be observed at the time of disposal, as they bring a lot of damage to public health and the environment. These wastes are classified into five distinct groups being A - Biological, B - Chemical, C - Radioactive, D - Common, and E - Sharps. In this sense, this work proposes a model for managing Health Service Waste generated in home care in the city of Apucarana - PR, after carrying out a diagnosis of generation and disposal. The sample included the participation of 135 patients who generated WHS with biological risk at home. It was observed that 34% of respondents had no knowledge about WHS, 43.6% discarded WHS in the common garbage and only 1% returned the RSS to the Basic Health Units. Among those interviewed, 78.7% never received material or training on the disposal of WHS. Disposal practices of WHS generated in household health activities have not been widely reported in the Municipality of Apucarana, furthermore, there is no published report of damage associated with this potentially hazardous waste stream in homes and the community. There is also no policy that specifically addresses the handling of domestic medical waste. All necessary techniques are clearly established in current federal regulations, such as Anvisa RDC 306/2004 and Conama 358/2005. Specific policies are needed and should include the responsibilities of family members, healthcare professionals, district assemblies, waste management companies and other interested parties. Sanctions for non-compliance must be specified and known to the public to increase compliance. Public implementation guidelines should include how to safely separate waste categories at source. Thus, it can be concluded that there is a lack of encouragement of professionals regarding correct guidelines, management by the Autarchy, updating of the system's database, organization, financial resources and environmental awareness regarding the risks of undue disposal of RSS.